Falkner-skan solution for gravity-driven film flow of a micropolar fluid (Penyelesaian Falker-Skan bagi Aliran Filem Graviti-Terpacu dalam Bendalir Mikrokutub) - Ahmad, Kartini; Nazar, R.; Pop, Ioan (Penerbit UKM, 2011)
The resulting nonlinear ordinary differential equations are solved numerically using an implicit finite-difference scheme. The results obtained for the skin friction coefficient as well as the velocity and microrotation or angular velocity profiles are shown in table and figures for different values of the material or micropolar parameter K.